KONTRIBUSI TAREKAT TIJANIYAH TERHADAP PERUBAHAN PRILAKU SOSIAL JAMA'AH MASYARAKAT DI DESA PAYABENUA - Ratna Dewi (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
The tijaniyah tarekat was founded by sheikh Abul Abbas at-Tijani, he came from the descendants of the Prophet Muhammad. In studying the tijaniyah tarekat he made a spiritual journey to Fez Morocco in 1171/1757 to study three tarekat namely the Qadiriyah, the Nashiriyah and the Ahmad bin al-habib tarekat. He received his first education from his father and from several other scholars until the age of 20-21 years. Then studied in other cities such as Algeria, Cairo, Makkah and Medina and met with several sheikhs including Sheikh Muhmud al-Karoli and Sheikh Abd. Karim Al-Sama (Samaniyah). These sheikhs contributed significantly to al-Tinjani's involvement in the tarekat movement. So it was from here that Sheikh Ahmad Tijani established a tarekat and this order was known as the tijaniyah tarekat. So that it spread very widely to the Eastern region, North Africa, India, Iran, Turkey, Egypt, and other countries including Indonesia, one of which was the Tijaniyah Order which was founded. In this regard, this problem needs to be examined regarding the tijaniyah tarekat